Monitoring of Animal Products Entering East Kalimantan with Total Plate Count Test - Faizal Rafiq; Dian Rahmawati; Dwi Untari; Dinar Puspitasari Susilo; Rini Nilamsari; Sri Sumarsih Lesari (Journal of Applied Veterinary Science And Technology, 2024)
Background: Quarantine measures on animal products that are transported between areas are prioritised at the place of export. It is necessary to establish a supervisory system through monitoring the entry of animal products. Purpose: Monitoring of animal products as food is carried out as an evaluation and consideration for further quarantine measures as well as for monitoring food safety aspects. Method:  The test conducted on the samples taken was the Total Plate Count (TPC) test. A total of 32 chicken meat samples, 31 meat samples (1 lamb and chevon sample, 10 buffen samples, 29 beef samples), 23 chicken sausage samples, and 18 beef sausage samples.  Results:  A total of 21 samples (91.60%) of chicken sausage TPC test results in comply with SNI and 2 samples (8.70%) TPC test results do not comply with SNI. Fifteen samples (83.33%) of beef sausage TPC test results in comply with SNI and 3 samples (16.67%) TPC test results do not comply with SNI. A total of 32 chicken meat samples, 1 lamb and chevon sample, 10 buffen meat samples, 29 beef samples the TPC test results were 100% in compliance with SNI 7388:2009. Conclusion:  This can be caused by sanitation and hygiene of handling and storage, temperature on the conveyance when being transported and storage temperature, product packaging. There was a break when the unloading officer took a break. This condition causes the commodity to stay too long in the open container and the temperature becomes less stable. This is thought to be due to handling during distribution, instability of storage temperatures and the perishable nature of processed meat products.